analysis of the objetives at the tall level commission not corruption front at the be able to of the corruption - Ramírez Tabraj, Eudosio (2017)
The work of investigation with the title: ANALYSIS OF THE OBJETIVES AT THE TALL LEVELCOMMISSION NOT CORRUPTION FRONT AT THE BE ABLE TO OF THE CORRUPTION, have motivedfor as much as the corruption every day tak bigger strength at detriment of the population. Allthe institutions publics government to be infected for the virus denominted corruption, at furtherinclusive the articles contener in the INTERAMERICAN CONVENTION AGAINST AT THE CORRUPTION,not cumpled at the whole, for as muc as not pud see the reflected of the prevention, sanction of thecorrups acctions, at the persons what to develop corrup actions.